FAKTOR-FAKTOR YANG MEMPENGARUHI PROGRESIVITAS KELOMPOK TANI LAHAN PANTAI DI KABUPATEN TAKALAR - Sartini Salam (Teknosains, 2011)
The objective of this study is to identify: (1) the factors which influenced the progressiveness of coastal land farmer groups in Takalar Regency, (2) the most significant factor which inf-luenced. The study was conducted at Takalar Regency by taking 30 farmer groups in Galut Sub-Regency (15 groups/4 vil-lages), Galsel Sub-Regency (3 groups/1 village), Mappaka-sunggu Sub-Regency (8 groups/3 villages), and Sanrobone Sub-Regency (4 groups/2 villages). Analysis of descriptive, multiple linear reg-ression, and path analysis are used in this study. The prog-ressiveness of coastal land farmer groups in Takalar Regency is influenced by the role of extension worker, groups leadership, cohesiveness of groups and the role ofvillage government officer. Key words: progressiveness, farmer groups, coastal land.